Comparison of Different Metrics for the Identification of Vascular Changes in Diabetic Retinopathy Using OCTA - Mendes, Luis; Marques, Inês P.; Cunha-Vaz, José (Frontiers in Neuroscience, 2021)
Retinal vessel metrics identifying microvascular changes such as vessel closure (VC) have shown potential clinical value by identifying eyes with diabetic retinopathy at different severity levels and at increased risk for disease progression to more severe stages. We compare the performance of 11 different metrics, which includes two metrics supplied by the manufacturer, based on OCTA for identification of VC in different ETDRS severity groups. OCTA en-face slabs from 84 healthy eyes (70±4.8 years) and 78 eyes of diabetic individuals (67±7.5 years) were processed using different methods that include: abnormal intercapillary spaces (AIS), vessel density (VD) and 9 metrics extracted from the en-face slab. The best separation between the eyes from diabetic individuals and the control group was obtained in the superficial capillary plexus (SCP), with the full retina also performing well. In the SCP the metrics that show better performance were the AIS and the VD with a value of AUC equal to 0.89 [CI 95% 0.84 -0.94] and 0.85 [CI 95% 0.79 -0.91], respectively, indicating that the VD metric supported by the manufacturer is satisfactory. The values of these metrics on the different ETDRS groups show a progressive increase in VC which is correlated with disease severity.